Pentingnya Pendidikan Etika Profesi Hukum bagi Anggota Polri dalam Mewujudkan Penegakan Hukum yang Adil - Irawan Kusumo; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Fair law enforcement in Indonesia highly depends on the integrity and professionalism of the Indonesian National Police (Polri) members. One of the key factors in shaping the character and professionalism of Polri is legal professional ethics education. This education plays a role in teaching Polri members not only to master the law technically but also to instill moral values and principles of justice in their actions. This study aims to analyze how legal professional ethics education can influence the quality of fair law enforcement by Polri. The author uses a normative research method with a quantitative approach to analyze secondary data related to the implementation of ethics education within the Polri institution. The results of the study indicate that legal professional ethics education has a positive impact on improving integrity, reducing abuse of power, and forming the professional attitude of Polri members, which in turn contributes to creating more just and transparent law enforcement. Therefore, strengthening legal professional ethics education within Polri is crucial to realizing a more just and trustworthy law enforcement system.